Features of the crisis 40 years for women and men (Actual Problems of Psychology in Educational Institutions, 2019)
Тhe period of maturity is called the "Golden" period ofpersonality development, characterized by progressive changes and the peak ofcreative productivity. Some scientists call the crisis of forty years the mostdangerous period of maturity. This article highlights the understanding of theconcept of "crisis of forty years" in the concepts of various researchers, as wellas the causes and symptoms of the crisis in men and women. In the event of acrisis of 40 years, a person has to once again rebuild his life plan, to develop alargely new "I"-the concept. This crisis can be associated with serious changesin life, up to the change of profession and the creation of a new family.
Keywords: «криза», «симптоми кризи», «криза сорока років», «причини кризи».